2017
DOI: 10.1021/acs.jmedchem.7b01135
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of 3-((4-Chloro-3-methoxyphenyl)amino)-1-((3R,4S)-4-cyanotetrahydro-2H-pyran-3-yl)-1H-pyrazole-4-carboxamide, a Highly Ligand Efficient and Efficacious Janus Kinase 1 Selective Inhibitor with Favorable Pharmacokinetic Properties

Abstract: The discovery of a potent selective low dose Janus kinase 1 (JAK1) inhibitor suitable for clinical evaluation is described. As part of an overall goal to minimize dose, we pursued a medicinal chemistry strategy focused on optimization of key parameters that influence dose size, including lowering human Cl and increasing intrinsic potency, bioavailability, and solubility. To impact these multiple parameters simultaneously, we used lipophilic ligand efficiency as a key metric to track changes in the physicochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The IC 50 values and molecular structures are shown in Table S1. Moreover, we downloaded three sets of inactive molecules from ZINC, which contained 2000, 10,000, and 20,000 molecules. …”
Section: Methodsmentioning
confidence: 99%
“…The IC 50 values and molecular structures are shown in Table S1. Moreover, we downloaded three sets of inactive molecules from ZINC, which contained 2000, 10,000, and 20,000 molecules. …”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking of ZT55 into the three-dimensional X-ray structures of JAK family members (JAK1, PDB code: 5WO4; JAK2, PDB code: 5UT6; JAK3, PDB code: 5TTU) was simulated using the graphical user interface DS-CDOCKER with Discovery Studio [1315]. The protein active sites for docking were determined from the inhibitor binding sites in co-crystal structures of the protein complexes retrieved from the RCSB Protein Data Bank.…”
Section: Methodsmentioning
confidence: 99%
“…These results correspond to the IC 50 values of pyrazolone derivatives consisting of chloro-methoxyphenyl-amino groups (19 nM) and pyrrole carboxamide (20 nM) toward JAK2 from previous reports. 48,49 The IC 50 values of the three mentioned compounds toward JAK3 were 18.90 ± 1.13 nM for 3h, 18.42 ± 0.34 nM for TK4b, and 15.80 ± 0.81 nM for TK4g. Previous reports showed that an aminopyrazole analogue with three chlorine atoms, which is to some extent similar to compound 3h compound, gave IC 50 values toward JAK2 and JAK3 of 2.2 and 3.5 nM, respectively.…”
Section: Virtual Screeningmentioning
confidence: 97%